Metabolic, cognitive and neuromuscular responses to different multidirectional agility-like sprint protocols in elite female soccer players - a randomised crossover study - Raeder, C.; Kämper, M.; Praetorius, A.; Tennler, J.-S.; Schoepp, C. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Purpose Resistance to fatigue is a key factor in injury prevention that needs to be considered in return-to-sport (RTS) scenarios, especially after severe knee ligament injuries. Fatigue should be induced under game-like conditions. The SpeedCourt (SC) is a movement platform for assessing multidirectional sprint performance, typical of game-sports, due to change-of-direction movements in response to a visual stimulus. Designing adequate fatigue protocols requires the suitable arrangement of several loading variables such as number of intervals, sprint distance or work/relief ratio (W:R). Therefore, this study analysed the acute fatigue effects of different SC protocols on metabolic load, cognitive function and neuromuscular performance.